Mathematical Connections in Preservice Secondary Mathematics Teachers' Solution Strategies to Algebra Problems - Vesife Hatisaru; Kaye Stacey; Jon Star (Sociedad Española de Investigación en Educación Matemática, 2024)
This study investigated the mathematical connections found in the solutions provided by 22 preservice secondary mathematics teachers to a set of algebra problems. Interest in, and research on, mathematical connections has gained prominence of the past decade. Here, we use the Extended Theory of Mathematical Connections or ETMC to explore the types of connections that this framework does and does not capture in the preservice teachers' solutions. The ETMC surfaced four types of mathematical connections across four problems: 'different representations', 'procedural', 'part-whole' and 'meaning'. The other types of connections defined in ETMC such as 'reversibility' or 'feature' were not found in our data, perhaps because of the specific problems that were used. Some mathematical connections were not highlighted when examining the solutions through the lens of ETMC ('meaning', 'implication or if/then' and modelling) addressing areas in which ETMC might be limited in its capacity to support researchers in identifying mathematical connections in different contexts.